2012
DOI: 10.13058/raep.2012.v13n4.79
|View full text |Cite
|
Sign up to set email alerts
|

Representações Sociais E Sustentabilidade: O Significado Do Termo Para Alunos Do Curso De Administração

Abstract: Fátima regina ney matos fneymatos@unifor.br universidade de fortaleza ana silvia roCHa ipiranga universidade estadual do ceará Diego De queiroz maCHaDo universidade de fortaleza germana Ferreira rolim universidade federal do ceará raFaella alves meDeiros alvarenga universidade de fortaleza resumo Considerando as atuais discussões sobre sustentabilidade, desenvolvimento, desenvolvimento sustentável e tendo como base a abordagem da teoria das representações sociais, o objetivo desse estudo foi identificar os sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
1
9
0
3
Order By: Relevance
“…Moreover, the results are in line with previous studies, which also have found that the socially shared knowledge is especially associated with the environmental dimension of sustainability (MATOS et al, 2012;RAMOS;KAYAMURA, 2009). However, our results indicate a movement of transformation of the representation of sustainability by including, albeit in the periphery, issues associated with awareness, responsibility, balance, and concern for the future.…”
Section: ≥ 10supporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the results are in line with previous studies, which also have found that the socially shared knowledge is especially associated with the environmental dimension of sustainability (MATOS et al, 2012;RAMOS;KAYAMURA, 2009). However, our results indicate a movement of transformation of the representation of sustainability by including, albeit in the periphery, issues associated with awareness, responsibility, balance, and concern for the future.…”
Section: ≥ 10supporting
confidence: 92%
“…A more recent study on the social representation of sustainability, performed by Matos et al (2012) with 132 students of Administration of a public university, found that the representation of sustainability was devised around the environment. As noted, the naturalist perspective of the concept of sustainability remains, dissociated from its socioeconomic dimensions, which, in some ways, is in line with the previous research.…”
Section: Social Representations and Sustainabilitymentioning
confidence: 99%
“…Although there are some investigations, the SRs about SD have been comparatively less analyzed. Among those studies, most have studied the perspectives of university students or professors, coming from different training areas (TECHIO; GONÇALVES; COSTA, 2016), or from different countries (RAMOS; KAWAMURA, 2009;BARTHES;JEZIORSKI, 2012;MATOS et al, 2012). The focus of these studies around the university population restricts the representativeness of the results since a wide probing of the views of different stakeholders it is not adequately ensured.…”
Section: Social Representations Of Sustainable Developmentmentioning
confidence: 99%
“…Moreover, there the purposes of the different research studies are diverse: some aim to identify the existing meanings of SD (e.g., TECHIO; GONÇALVES; COSTA, 2016;MATOS et al, 2012;RAMOS;KAWAMURA, 2009); others, intend to verify if the nationality of the participants (BARTHES; JEZIORSKI, 2012) or their area of training exert influence on the representations found; others, still, intend to detect the presence of contents related to Environmental Education in the surveyed representations of SD (FLORES; ROJAS, 2013;PONS-GUTIERREZ, 2013).…”
Section: Social Representations Of Sustainable Developmentmentioning
confidence: 99%
“…Assim, os autores puderam revelar processos intraindividuais, interindividuais e situacionais, sob a forma de sistemas de crenças, valores, símbolos e histórias que dão sentido à existência das organizações estudadas, de acordo com interpretações dos gestores. Matos et al (2012) procuraram identificar os significados da palavra sustentabilidade para alunos do curso de Administração de uma instituição de ensino superior pública, constatando a permanência da representação da sustentabilidade relacionada basicamente no meio ambiente e do significado naturalista do conceito e dissociado das demais dimensões do desenvolvimento sustentável. Miranda et al (2016) investigaram as representações sociais de vestibulandos quanto ao estereótipo tradicional do profissional contábil, caracterizado predominantemente como sendo um indivíduo do sexo masculino, conservador e pouco flexível, e como esta representação tende a se modificar em função das percepções dos futuros novos profissionais ingressantes nos cursos.…”
Section: A Perspectiva Da Teoria Das Representações Sociaisunclassified